THE ROLE OF AFRICA IN THE NEW MARITIME SILK ROAD - Pautasso, Diego (Brazilian Journal of African Studies, 2017)
The purpose of this paper is to analyze Africa’s role in the construction of the New Maritime Silk Road. This is just one of the vectors of the ambitious Chinese integration project in Asia, Europe and Africa, launched in 2013 under the title OBOR Initiative (One Belt, One Road). By overcoming the challenges of national reconstruction, China is becoming more assertive and shaping its global integration strategy. In this sense, the New Silk Road aggregates the main objectives of China’s diplomacy in the twenty-first century, elevating Africa to a springboard condition in order for the project to become global.